2020
DOI: 10.5194/tc-2020-19
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wave–sea-ice interactions in a brittle rheological framework

Abstract: Abstract. The decrease in Arctic sea ice extent is associated with an increase of the area where sea ice and open ocean interact, commonly referred to as the Marginal Ice Zone (MIZ). In this area, sea ice is particularly exposed to waves that can penetrate over tens to hundreds of kilometres into the ice cover. Waves are known to play a major role in the fragmentation of sea ice in the MIZ, and the interactions between wave-induced sea ice fragmentation and lateral melting have received particular attention in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 59 publications
1
30
0
Order By: Relevance
“…Answering this question requires the development of a coupled wave–ice-ocean modelling framework that is informed and validated with relevant and dedicated field studies, as well as the implementation of systematic observational products of MIZ dynamics. Efforts in this direction are well underway with the recent development of coupled wave–ice models [76] and remote sensing products of waves-in-ice [37,38] and floe size [77]. This review further highlights a number of specific questions and research avenues that are summarized below: A generalized rheological model should be applicable to any type of sea ice in both hemispheres.…”
Section: Discussionmentioning
confidence: 99%
“…Answering this question requires the development of a coupled wave–ice-ocean modelling framework that is informed and validated with relevant and dedicated field studies, as well as the implementation of systematic observational products of MIZ dynamics. Efforts in this direction are well underway with the recent development of coupled wave–ice models [76] and remote sensing products of waves-in-ice [37,38] and floe size [77]. This review further highlights a number of specific questions and research avenues that are summarized below: A generalized rheological model should be applicable to any type of sea ice in both hemispheres.…”
Section: Discussionmentioning
confidence: 99%
“…This concept of damage has clear parallels with the mechanism discussed above of how winter in-plane brittle fracture events can determine how the sea ice breaks up in summer and may therefore present a useful basis for the development of a full parameterisation of brittle fracture processes for use in FSD models. Boutin et al (2021) also demonstrated that the Maxwell-EB rheology can be combined with an FSD model in order to explore how wave break-up of floes can impact sea ice dynamics, highlighting an application of floe size modelling not considered in this study.…”
Section: Inclusion Of Brittle Fracture In Fsd Modelsmentioning
confidence: 98%
“…Their breakup parametrization was inspired by that of [12] and assumed an underlying Pareto distribution. Building further on their WW3 module, Boutin et al coupled it with the sea ice models LIM3 [52] and neXtSIM [54]. Even though the FSDs are evolved by the ice models, the wave-induced breakup is handled by WW3, which, for coherence, leads to convergence towards Pareto distributions.…”
Section: Theory Of Wave-induced Sea Ice Breakupmentioning
confidence: 99%